Evaluation of Superovulation Results on in Vivo Embryo Production in Three Different Cows Breeds at The Livestock Embryo Center - Rismasari; Dwi Wijayanti; Fahrudin Darlian; Putri Indah Ningtias; Andri Kusmayadi (Jurnal Peternakan Nusantara, 2026)
The purpose of this study was to compare the superovulation response in several breeds, namely Angus, Friesian Holstein (FH), and Ongole crossbreed (OC). A total of 152 cows were used in this study, namely 39 Angus cows, 62 Friesian Holstein cows, and 51 Ongole crossbreed cows. The parameters of this study were the number of CL, response rate, recovery rate, number of embryos collected (1, 2, 3, 4 (DG/UFO)), proportion of transferable embryos, proportion of DG, and proportion of UFO. The collected data were tested using the Kruskall-Wallis test, if there was a difference, it was continued using the Mann-Whitney test. The results of this study included the number of CL, recovery rate, total embryos collected, proportion of DG, and proportion of UFO of Angus, FH, and OC cows showed significantly different results (P <0.05), the response rate showed very significantly different results (P <0.01), but the proportion of transferable embryos was not significantly different (P > 0.05). This study concludes that CO cattle have the highest average of CL, response rate, recovery rate, and total embryos collected. Meanwhile, Angus cattle produce the lowest percentage of DG and UFO embryos